(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2023)
In this study, the researcher examine the commonalities and identities of several selected films to demonstrate the limits of the ’auteur theory’. This paper examines the filmmaker’s technical prowess, inner meaning, and personal style of his Karthik Subbaraj. This research paper will be analysing the director Karthik Subbaraj through the application of auteur theory. This will be done by using the movies Pizza(2012), Jigarthanda(2014), Iraivi(2015), Mercury(2017), Petta(2019), Jagame thandhiram(2021), Mahaan(2022) by author Karthik Subbaraj as samples for the study. The qualitative methodology will be used with content analyse on auteur theory and its three main components which are technical competence, personal style and inner meaning as proposed by Andrew Sarris (1962). How to cite this article: Irayanban AA. The Study on Auteur Film Director Karthik Subbaraj. J Adv Res Jrnl Mass Comm 2023; 10(1): 29-32. DOI: https://doi.org/10.24321/2395.3810.202306